2016
DOI: 10.3389/fonc.2016.00264
|View full text |Cite
|
Sign up to set email alerts
|

VDAC3 As a Potential Marker of Mitochondrial Status Is Involved in Cancer and Pathology

Abstract: VDAC3 is the least known isoform of the mammalian voltage-dependent anion selective channels of the outer mitochondrial membrane. It has been recently shown that cysteine residues of VDAC3 are found over-oxidized. The VDAC3 cysteine over-oxidation was associated with the oxidizing environment and the abundance of reactive oxygen species (ROS) in the intermembrane space. In this work, we have examined the role of VDAC3 in general pathogenic mechanisms at the basis of mitochondrial dysfunction and involving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 95 publications
0
52
0
Order By: Relevance
“…VDAC is the primary transport channel in the MOM, controlling mitochondria permeability and function. The vast majority of studies involving VDAC in a wide variety of mitochondria-associated pathologies focuses exclusively on VDAC1 or VDAC2, while VDAC3 channels remain poorly characterized (Shoshan-Barmatz and Ben-Hail, 2012; Reina et al, 2016b; Camara et al, 2017; Maurya and Mahalakshmi, 2017; Shoshan-Barmatz et al, 2017). The main reason for this discrepancy stems from the difficulty in obtaining stable and homogeneous VDAC3 samples for insertions in PLM, and thus the lack of quantitative in vitro characterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDAC is the primary transport channel in the MOM, controlling mitochondria permeability and function. The vast majority of studies involving VDAC in a wide variety of mitochondria-associated pathologies focuses exclusively on VDAC1 or VDAC2, while VDAC3 channels remain poorly characterized (Shoshan-Barmatz and Ben-Hail, 2012; Reina et al, 2016b; Camara et al, 2017; Maurya and Mahalakshmi, 2017; Shoshan-Barmatz et al, 2017). The main reason for this discrepancy stems from the difficulty in obtaining stable and homogeneous VDAC3 samples for insertions in PLM, and thus the lack of quantitative in vitro characterization.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Okazaki et al (2015) required reducing agents to observe proper VDAC3 gating. Similarly, the oxidation state of cysteines was found to be important for the insertion and activity of VDAC3 samples (Reina et al, 2016b). It must be pointed out that in these previous works, any reducing agent was avoided during purification and reconstitution steps, with the purpose of not altering the naturally occurring oxidation state of cysteines (Reina et al, 2016a; Saletti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another exciting possibility regarding regulation of the newly identified channels is that, similarly to VDACs, their activity depends on the oxidation state of the protein itself . Recent studies highlighted the role of cysteine oxidation in determining the pore size of the VDAC3 porin isoform, proposing that effective metabolite flux across these huge pores might be linked to the redox state in the intermembrane space of mitochondria.…”
Section: Questions To Be Answered and Future Challengesmentioning
confidence: 99%
“…For example, induction of ROS production by incubation of mitochondria, isolated from rat hearts, with the complex III inhibitor antimycin A, which results in O 2 ° − release to the IMS, led to oxidation of cysteines in IMS proteins such as TIMM50, VDAC3, OPA1 and AK2 (Bleier et al ., ). Oxidative modifications on VDAC3 but also VDAC2 were also reported by other studies (De Pinto et al ., ; Reina et al ., ). A different study characterizing IMS proteins as H 2 O 2 targets in yeast mitochondria identified IMS proteins such as Pet191 and cytochrome b 2 (Topf et al ., ).…”
Section: Cysteine Residues In Ims Proteinsmentioning
confidence: 97%